Agus Prasetyo Aktor dan Rol Wayang Orang Sriwedari - Dhestian Wahyu Setiaji; Sri Rochana Widyastutieningrum; Aminudin Aminudin (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2023)
Agus Prasetyo: Actors and Role of Wayang Orang Sriwedari is an analysis of a person’s character. Agus Prasetyo’s ability of acting and artistic process to become a role is interesting to study because his existence has an impact on the sustainability and development of the Wayang Orang Sriwedari. The problem that is revealed is how the process of Agus Prasetyo becomes a role and its impact in terms of the sustainability and development of the Sriwedari Wayang Orang. Habitus theory is used to examine Agus Prasetyo’s process as an actor. The text and context approaches are used to find factors that support Agus Prasetyo to be a role model. The data collection is carried out by using the methods of observation, literature studies and interview. The collected data is analyzed using a data analysis process that emphasizes interpretative descriptive. The analytical study finds that Agus Prasetyo’s process of becoming a wayang orang actor is obtained through an educational process in the family, school and environment. This analysis also reveals that Agus Prasetyo’s acting as a role is supported by his creative and improvisational abilities in applying tembung (words), tandang (work) and tembang (songs).